The Volunteers Phenomenon of Presidential Election in Indonesia - Elsa Septia; Suswanta Suswanta (Journal of Governance, 2022)
This study identifies the political influence of Jokowi Mania volunteers on the policies of President Joko Widodo Period II. Joko Widodo's election victories in 2014 and 2019 did not occur without the role of volunteers. This political volunteer movement emerged based on shared unrest and the people's sense of distrust of the democratic space, which is dominated by political parties and politicians who are problematic. This research uses qualitative research. The data collection technique was obtained by using the Ncapture feature on the Nvivo 12 plus, where the Ncapture feature is a web browser extension developed to capture web content in the form of website content, online media, and other document content such as scientific articles and collections of observers' opinions regarding the policies of President Joko Widodo. Based on the study results, four important points have been analyzed by researchers using crosstab on the Nvivo 12 Plus. The first is advocacy, with a percentage of 35.71%, the second is monitoring, with 21.43%, the third is the program, and the last is reconciliation, with 19.05%. The political policies carried out by Jokowi Volunteers also affect most of those who used to be policy volunteers are now part of the government and occupy strategic positions.